Barry Jones address to the National Press Club on 7 December 1994 - Jones, Barry, 1932-; Australia. Parliament. House of Representatives. Standing Committee for Long Term Strategies; National Press Club (Australia) (1994)
Hon. Barry O. Jones, Chairperson, House of Representatives Long Term Strategies Committee, discusses issues raised in the report, Australia's population carrying capacity', and encourages ongoing and informed community debate on population and resource use in Australia.
Photographs available.
Accompanied by: Australia's population carrying capacity' : one nation, two ecologies : report / by the House of Representatives Standing Committee for Long Term Strategies. Canberra : AGPS, 1994.
Also available online
Transcript available (typescript, 16 leaves)
Keywords: Jones, Barry, -- 1932-; Natural resources -- Australia; Australia -- Population; Australia -- Population -- Environmental aspects; Australia -- Population policy